Building sustainable historic centres: A comparative approach for innovative urban projects - Adriana Rabinovich; Andrea Catenazzi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Since the 1980s, the promotion of heritage values has gradually become a relevant issue for urban planning. Together with the emergence of new peripheries, inner-city areas and particularly old historic centres, affected by deterioration due to the recession of the last decades, have been the object of study and actions. Consequently, the need to turn the historic centres into areas of development for the market, through legislative measures and investments in infrastructure and services, and the re-evaluation of the heritage value of existing buildings, oscillated between policies which, linked to the mechanisms of economic and cultural globalization, promoted tourism as a source of revenue while striving to find alternatives to gentrification.
Keywords: O18; N90; 330; urban planning; innovative planning; urban governance; decision-making; sustainable development; historic centres; heritage values; access to the city; Kommunalverwaltung; Kommunalplanung; Stadtgeschichte; Nachhaltige Entwicklung; Stadtentwicklung